2020
DOI: 10.1007/s00281-020-00821-0
|View full text |Cite
|
Sign up to set email alerts
|

Shelter from the cytokine storm: pitfalls and prospects in the development of SARS-CoV-2 vaccines for an elderly population

Abstract: The SARS-CoV-2 pandemic urgently calls for the development of effective preventive tools. COVID-19 hits greatly the elder and more fragile fraction of the population boosting the evergreen issue of the vaccination of older people. The development of a vaccine against SARS-CoV-2 tailored for the elderly population faces the challenge of the poor immune responsiveness of the older population due to immunosenescence, comorbidities, and pharmacological treatments. Moreover, it is likely that the inflammaging pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 130 publications
(135 reference statements)
0
49
0
2
Order By: Relevance
“…The composition of the GM differs between individuals and has emerged as an important immune modulator, closely associated with an individual’s health, including the risk of disease development. The cross-talk between the GM and the host’s immune system is achieved through molecular interactions after bioactive metabolites (short-chain fatty acids) are produced or through interactions with the host’s immune cells through cell-surface molecules (peptidoglycans and lipopolysaccharides) [ 10 , 18 , 19 , 20 ]. Notably, recent studies have reported the effects of the GM on the response to vaccination, including its stimulation of specific CD8 + -cell differentiation, B-lymphocyte growth and differentiation, and production of specific immunoglobulin A molecules (IgAs) [ 21 , 22 , 23 , 24 ].…”
Section: Interplay Between Gut Microbiota and Immunity In The Eldementioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the GM differs between individuals and has emerged as an important immune modulator, closely associated with an individual’s health, including the risk of disease development. The cross-talk between the GM and the host’s immune system is achieved through molecular interactions after bioactive metabolites (short-chain fatty acids) are produced or through interactions with the host’s immune cells through cell-surface molecules (peptidoglycans and lipopolysaccharides) [ 10 , 18 , 19 , 20 ]. Notably, recent studies have reported the effects of the GM on the response to vaccination, including its stimulation of specific CD8 + -cell differentiation, B-lymphocyte growth and differentiation, and production of specific immunoglobulin A molecules (IgAs) [ 21 , 22 , 23 , 24 ].…”
Section: Interplay Between Gut Microbiota and Immunity In The Eldementioning
confidence: 99%
“…Consequently, fewer naïve T cells are produced with time, and T-cell receptor variants become unable to diversify and respond to newly encountered antigens. Similarly, the ability of B cells to produce immunoglobulin also declines with age, as do the activities of neutrophils and natural killer (NK) cells [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Thus, the elderly is disproportionately affected by infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within such a complex scenario, recent advances in systems biology, integrating clinical, immunologic, and omics data can help to identify stable and robust markers of vaccine response and move towards a better understanding of SARS-CoV-2 vaccine responses in the elderly (See [8,16,24] in this issue). In particular, motivated by the still unclear immunopathological mechanisms of SARS-CoV-2 infection, Ciabattini et al stress that the design of vaccination strategies for older people is extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among the different SARS-CoV-2 vaccine platforms that have been developed, only a few are being tested in the older fraction of the population. Ciabattini et al conclude that systems biology will help in addressing the complexity of this topic and in better understanding SARS-CoV-2 vaccine responses in the elderly ( [24] in this issue).…”
Section: Introductionmentioning
confidence: 99%